2022
DOI: 10.31004/cendekia.v6i2.1384
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pemahaman Konsep Geometri Transformasi dalam Penerapan Etnomatematika Budaya Batik Tulis Tanjung Bumi

Abstract: Matematika merupakan salah satu cabang ilmu yang memiliki peran dalan kehidpuan. Pada pembelajaran matematika saat ini tetap berpusat pada guru, sehingga siswa cenderung pasif dalam berinteraksi, dan hanya menunggu sajian materi dari guru, tanpa mencari pengetahuan secara mandiri. Berdasarkan observasi dilapangan, siswa kelas XII IPA 4 di SMA Negeri 1 Ketapang menunjukkan bahwa hampir 85% siswa mengalami kesulitan pelajaran matematika materi geometri transformasi. Kesulitan yang dihadapi oleh siswa adalah meng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…1, 2, 3 (Andelia et al, 2022) The results of this study showed that in Tanjung Bumi batik there are concepts of geometric transformation, including the concept of translation in the Rhombus batik motif, the concept of reflection in the Triangle batik motif, and the concept of rotation in the square batik motif. 1, 2 (Astuti et al, 2019) The results of this study showed that there is a concept of number patterns in the motifs of Adipurwo batik.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…1, 2, 3 (Andelia et al, 2022) The results of this study showed that in Tanjung Bumi batik there are concepts of geometric transformation, including the concept of translation in the Rhombus batik motif, the concept of reflection in the Triangle batik motif, and the concept of rotation in the square batik motif. 1, 2 (Astuti et al, 2019) The results of this study showed that there is a concept of number patterns in the motifs of Adipurwo batik.…”
Section: Resultsmentioning
confidence: 82%
“…Thus, ethnomathematics-based learning can be an interesting learning alternative for students. (Andelia et al, 2022) Tanjung Bumi Batik Motif Applied to class XII IPA 4 at SMAN 1 Ketapang when learning geometric transformation material (Nurmanitia et al, 2023) Kawung Batik Motif Applied to class IV at SDN 1 Kiringan Klaten when learning the material of the perimeter and area of plane shapes Based on the articles reviewed by the researchers, traditional batik can be implemented in learning mathematics through contextual teaching and learning (CTL). CTL is a learning method that connects the learning materials with reallife situations (Abi, 2017).…”
Section: The Application Of Traditional Batik In Mathematics Learningmentioning
confidence: 99%
“…Etnomatematika adalah kata yang digunakan untuk menunjukkan keberadaan gagasan dan komponen matematika budaya (Kholifah et al, 2022). Selaras dengan yang dikatakan oleh (Hardiarti, 2017) etnomatematika merupakan istilah untuk menyebutkan matematika dalam budaya.…”
Section: Pendahuluanunclassified